Smart Garden System Based on Internet of Things using NodeMCU ESP8266 - Mukhlis, Waldy; Yohandri, Y; Yulkifli, Y; Mairizwan, M (Department of Physics – Universitas Negeri Padang UNP, 2023)
Gardening is an agricultural sector that requires control and monitoring of work. However, the management and monitoring are still done manually. Therefore, we developed an internet of the things-based smart garden to monitor and control plants. This study aims to determine the design and performance of the system. This research is a type of engineering research. The measurement technique is to measure directly by comparing air humidity, air temperature, soil moisture, and soil temperature with the standard tool. The indirect measurement is by analyzing the value of accuracy and precision of the instrument. The system uses a DHT11 sensor measuring air temperature and humidity, a soil moisture sensor, and a DS18B20 sensor to measure soil temperature. The device has nearly 100% accuracy in all parameters, especially in the range of 93.53% to 98.61%. Precision for all parameters of the selected devices is also close to 100% in the range of 98.6% to 99.8%. Based on these results, the design of the smart garden tool can work well